Creep-feeding young lambs - Galal, E.S.E.; Gojam, Y.; Wolde-Gabriel, K. (1981)
A trial was conducted on 26 male twin lambs to study the effect of creep feeding on lamb development and growth Creep feeding started when the lamb’s average age was 43 days. Lambs were weaned at an average age of 93 days. The creep feed group was fed ad libitum until the age of six months while the other group was given 200 g/head/day of concentrates plus hay ad libitum. The preweaning average concentrate consumption by the creep fed group was 284 g/head/day and the postweaning consumption of the same group was 495 g/head/day. Weaning and 6 month weights were higher (p< .01) in the creep-fed group than the control one (16.7 vs 14.6 and 27.7 vs 17.8, resecti vely). Averge daily gains followed the same trend. The post weaning concentrate feed conversion ratio in the creep fed group was 4.19 while that in the control group was 4.88. The return in terms of body weight gain, on the extra ration input in the creep-fed group was 3.83 kg for each 1 kg of extra ration.